College students’ stress and health in the COVID-19 pandemic: The role of academic workload, separation from school, and fears of contagion - Yang, Chunjiang; Chen, Aobo; Chen, Yashuo (PloS one, 2021)
The COVID-19 pandemic has unhinged the lives of people across the globe. In particular, more than 30 million Chinese college students are home-schooling, yet there is little understanding of how academic workload, separation from school, and fears of contagion lead to a decrease in their health. This study examined the relationships between Chinese college students’ three critical stressors and two types of health in the COVID‐19 pandemic context. We used a three-wave lagged design with a one-week interval. All the constructs were assessed by self-report in anonymous surveys during the COVID‐19 pandemic. College students were asked to report their demographic information, academic workload, separation from school, fears of contagion, perceived stress, and health. The results of this study showed that academic workload, separation from school, and fears of contagion had negative effects on college students’ health via perceived stress. In the COVID-19 crisis, multiple prevention and control measures focusing on college students may lead them to have different degrees of stress and health problems. Our results enrich the literature on stress and health and offer novel practical implications for all circles of the society to ensure students’ health under the context of the COVID-19 epidemic.